Reduction in paediatric intensive care admissions during COVID-19 lockdown in Maryland, USA - Ana Lia Graciano; Adnan T Bhutta; Jason W Custer (BMJ Publishing Group, 2020)
As a public health measure during the COVID-19 pandemic, governments around the world instituted a variety of interventions to 'flatten the curve'. The government of Maryland instituted similar measures. We observed a striking decline in paediatric intensive care unit (PICU) admissions during that period, mostly due to a decease in respiratory infections. We believe this decline is multifactorial: less person-to-person contact, better air quality and perhaps 'fear' of going to a hospital during the pandemic. We report an analysis of our PICU admissions during the lockdown period and compared them with the same time period during the four previous years.